Strong and \(Δ\)-Convergence for Asymptotically \(k\)-Strictly Pseudo-Contractive Mappings in CAT(0) Spaces - Pakkaranang, Nuttapol; Kumam, Poom (Communications in Mathematics and Applications, 2016)
In this paper, we study and prove fixed point and convergence theorems for asymptotically \(k\)-strictly pseudo-contracttive mappings in CAT(0) spaces. Our result extend and improve many results in the literature.